HUBUNGAN PENGETAHUAN, KONSUMSI CAIRAN DAN STATUS GIZI DENGAN STATUS HIDRASI PADA KURIR EKSPEDISI - Kurniawati, Fitri; Sitoayu, Laras; Melani, Vitria; Nuzrina, Rachmanida; Wahyuni, Yulia (JURNAL RISET GIZI, 2021)
Background: Hydration results from body fluids balance, while dehydration results from body fluids imbalance. Dehydration can result from losing too much water, not drinking enough or both of these things. There are certain job who has  special needs for fluids especially who works in hot environments.Objective: To determine the relationship between knowledge, fluid intake and nutritional status with hydration status in expedition couriers.Methods: A cross-sectional design with 44 expedition couriers as the research subject. Knowledge of fluids were obtained using a questionnaire, fluid intake were obtained by interview using repeated 24-h food recall, nutritional status were obtained by using BMI and the hydration status were obtained by urine specific gravity using urinalysis reagent strips. The data was processed and analyzed using Pearson correlation test.Results: Most of the respondents had sufficient knowledge (59.1%). The average fluid intake of the respondents were 2562 mL. Most of the respondents had normal nutritional status (45.4%). Almost half of respondents has pre-dehydration (45.5%). There  were arelationship between knowledge of fluids and hydration status (p=0,0001, r=-0,514), also between fluid intake and hydration status (p=0,0001, r=-0,685). There is no relationship between nutritional status and hydration status (p=0,337, r=0,148).Conclusion: Fluid intake and hydration status on expedition couriers are still not as expected, even though expedition couriers have sufficient knowledge.